PENGARUH PENERAPAN SISTEM INFORMASI MANAJEMEN NIKAH DAN PENGENDALIAN INTERNAL TERHADAP EFEKTIVITAS KERJA PEGAWAI PADA KANTOR URUSAN AGAMA (KUA) - Egi Zaenal Mutaqin (Journal Of Regional Public Administration (JRPA), 2019)
This study generally aims to analyze the Effect of application of the Marriage Management Information System and internal control over employees work Effectiveness in the Religious Affairs office, North Sumedang sub-district,, Sumedang District. The research method used in this study is descriptive analysis method, the research variables consists of independent variable, namely the Application of Marriage Management Information System and Internal Control, and the dependent variable is the employees Work Effectiveness in the Religious Affairs Office,North Sumedang sub-distric, sumedang district. The study population is 42 employees using the census. The analysis used in this study is multiple regression analysis simultaneously the results of the study show that the Application of Marriage Management Information System (X1) and Internal Control (X2) has an effect on Employees Work Effectiveness (Y) of 64.80% while the remaining 35.20% is influenced by other variables from outside the variable Implementation of the Management and Internal Control Information System which is not included in the model. Partially the Application of Marriage Management Information System (X1) has an effect on Employee Work Effectiveness (Y) from 30.20% from the criteria of 100%. Then Internal Control (X2) has an effect on Employees Work Effectiveness (Y) of 41.96% from the criteria of 100%. To find out the main hypothesis the formulation is tested by using multiple regression testing, based on the testing obtained F count value is greater than F table that is F count 23,398> F table 3,244 from the value obtained, that Ho decision is rejected, so it concludes variable Application of Marriage Management Information System and Internal Control (X2) significantly and positively influences the variable Employees Work Effectiveness (Y).